(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
In a rapidly globalising economy, enterprises seeking to raise their economic potential must adopt advanced practices proven in foreign contexts. “Economic potential” of an enterprise can be understood as its capacity to generate sustainable value growth, enhance competitiveness, and adapt to changing environments. This paper surveys selected foreign practices — institutional, strategic and operational — which, when adapted appropriately, may bolster enterprise economic potential. The focus is on: (1) improving the business environment and governance, (2) strategic integration into global value chains and innovation ecosystems, and (3) human capital, institutional partnerships and organizational learning. We conclude with recommendations for how enterprises in transition economies may internalise these practices.